(untitled) (Research, Society and Development, 2023)
This article emphasizes the importance of Inorganic Chemistry in high school education, encompassing the structure of elements to practical applications of chemical reactions, crucial for understanding interactions in nature and industry. The main objective is to clarify its relevance, providing an in-depth analysis ranging from element organization to the practical implications of chemical reactions. Configured as a narrative literature review, it seeks to shed light on the significance of Inorganic Chemistry in various fields, including industry and daily life, establishing interdisciplinary connections with Physics, Biology, and Geology. Education extends beyond theory, promoting the development of analytical skills through practical activities. It argues that Inorganic Chemistry is not merely a set of theories but a discipline that permeates daily life, providing a foundation for a deeper understanding of the world. Its continuity in education is crucial not only for academic formation but also for fostering a more informed and conscious society. The conclusion drawn is that an interdisciplinary approach enriches students’ comprehension and develops practical skills, contributing to academic formation and preparing them for current challenges, along with suggestions for innovative teaching methods.